Eksplorasi Mikroflora Alami Cairan Nepenthes mirabilis (Lour) Druce di Kawasan Hutan Penelitian dan Pendidikan Biologi Universitas Andalas - Titami, Hania; Periadnadi, Periadnadi; Nurmiati, Nurmiati (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Indonesia is a country that is rich in flora and fauna diversity, one of the unique flora in Indonesia is Nepenthes. This bag serves to trap insects or other small animals, the Biology Education and Research Forest (HPPB) is located in the Andalas Limau Manis University campus area which is classified as lowland tropical rain forest which is the habitat of Nepenthes, in the Biology Education and Research Forest (HPPB) this type of pitcher plant, namely Nepenthes mirabilis. Nepenthes mirabilis is a plant that is able to digest insects trapped in pockets at the ends of its leaf tendrils, so it is classified as a carnivorous plant. Microorganisms play an important role in breaking down organic materials into inorganic ones available to plants. Types of bacteria and bacterial populations greatly determine the decomposition process of animals that have been trapped in the bag as a source of nutrients for Nepenthes plants. This study aims to explore the natural microflora of Nepenthes mirabilis fluids, determine the proportional presence of potential bacteria, and determine the in vitro potential of chitinolytic bacteria from Nepenthes mirabilis fluids. This study used a survey method which was analyzed descriptively. The results showed that Nepenthes mirabilis fluid contained the presence of Fermentative, Amylolytic, Proteolytic, Chitinolytic and Lipolitical bacteria. Nepenthes mirabilis liquid in open bags contained chitinolytic bacteria, the highest presence of chitinolytic bacteria was found in MBB samples (20,104 cfu/ml) and MBA samples (18,104 cfu/ml). .28), fermentative (2.33 and 2.00), amylolytic (1.42 and 1.28), proteolytic (2.00 and 2.00), lipolytic (1.75 and 1.28).